Effect of head position on centre of mass variability during handstand: preliminary results - Farana, R.; Brtva, P.; Irwin, G. (ISBS Proceedings Archive (Michigan), 2023)
The aims of this study were: a) to determine to determine the change in joint angle kinematic variability during the handstand with different head positions, and b) to determine the contributions made by wrist, shoulder, and hip joint angles variability on CoM variability in handstand. Four young active female gymnasts performed 3 trials of handstands with three head positions (normal, straight, and flexed). 3D kinematics were collected for each trial. Statistical differences were analysed using One-way ANOVA and effect sizes (ES) reported. Forward stepwise regression was carried out between CoM variability and joint angle variability. The prevalent control strategies were at the shoulder with straight and flexed head position, and hip strategy in normal head position.